Annotated record of the detailed examination of Mn deposits from MIDPAC-1 expedition with RV Sonne (SO18) - Peter Halbach; Frank T Manheim (PANGAEA, 2023)
The dredges, free-fall grabs, cores and camera sled photographies described in this report were taken during the Midpac extquotesingle81 expedition with RV Sonne (SO 18) in the Pacific Ocean.